Growth, Immunity, and Transcriptome Response to Dietary Wnt/β-Catenin Pathway Activator TWS119 in Penaeus vannamei - Hou, Cuihong; Song, Shougang; Zhu, Lulu; Shi, Lili; Tan, Beiping; Zhang, Shuang (Frontiers in Marine Science, 2021)
Wnt/β-catenin signalling plays an essential role in the immunity of Penaeus vannamei. In this study, the effects of dietary Wnt/β-catenin pathway activator TWS119 on the growth, immunity, and transcriptome response in P. vannamei were investigated. Penaeus vannamei were fed diets with added TWS119 at doses of 0 (T0), 0.25 (T0.25), 1 (T1), 4 (T4), 16 (T16), or 64 mg·kg−1 (T64), respectively. LvGSK3β activity was effectively inhibited in P. vannamei given TWS119. The growth of P. vannamei in the T16 group was significantly improved when compared with the control group. After Vibrio parahaemolyticus infection, the survival rates (SRs) of P. vannamei in all experimental groups except the T64 group were significantly higher than in the T0 group. Compared with the control group, the immune enzymes’ activities in the serum of P. vannamei increased in all the experimental groups, while the malondialdehyde (MDA) contents decreased. Transcriptome analysis identified 5,073 differentially expressed genes (DEGs) for P. vannamei in the T0 and T16 groups. Most of the DEGs are involved in the ribosome pathway, endocytosis, glycerophospholipid metabolism, Wnt signalling, and FoxO =signalling pathways. The majority of the DEGs were from the ribosome pathway, which is also the most significantly enriched pathway. The study confirmed that the growth and immunity status of P. vannamei could improve by increasing dietary TWS119, which probably regulates the activity of the Wnt/β-catenin pathway and may be closely related to ribosome function and energy metabolism.